Peran Kepala Desa dalam Alokasi Dana Desa di Bidang Infrastruktur - Melia Sintha; Robert Caniago (Resolusi: Jurnal Sosial Politik, 2020)
This research is located in Kalapeh Baru Village, Sumber Barito District, Murung Raya Regency. The research was conducted with the aim of finding out the role of the Village Head in managing the Village Fund Allocation, especially in the field of infrastructure in the Kalapeh Baru Village. The research findings show that the role of the village head is going well. The role of the Village Head in village financial management, including Village Fund Allocation as stipulated in the Minister of Home Affairs Regulation No. 20 of 2020 in Chapter IV on Management states that village financial management consists of planning, implementation, administration, reporting and accountability in Kalapeh Village It's just been going well. The inhibiting factor in the Village Head managing the Village Fund Allocation in Kalapeh Baru Village consisted of a lack of cooperation from the community and also the State Ministry of Village Consultative. In addition, the supporting factor is the realization of the budget can run on time, as well as full support from the Regional Government of Murung Raya Regency.